Marketing essentials for independent lodgings - Lanier, Pamela, (Tourism and hospitality management collection., 2017)
Marketing a small, independently owned lodging business can be difficult. Marketing Essentials for Independent Lodgings outlines how to get a business's name out there, attract consumers, and navigate the dicey world of social media and an online presence. Descriptions of traveler demographics, how to get the word out about a property, and how to make a property unique are all talked about at depth. The goal of this book is to help small lodgings flourish, and it does so by including lists of actions that can be taken this week, this month, or this year to help positively impact the bottom line. Also included is a specific marketing outline that can be adapted to an individual business, giving business owners a timeline and plan they can follow.